2022
DOI: 10.48550/arxiv.2206.09950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining R$_V$ Variation Using Highly Reddened Type Ia Supernovae from the Pantheon+ Sample

Abstract: Type Ia supernovae (SNe Ia) are powerful tools for measuring the expansion history of the universe, but the impact of dust around SNe Ia remains unknown and is a critical systematic uncertainty. One way to improve our empirical description of dust is to analyse highly reddened SNe Ia (𝐸 (𝐵 − 𝑉) > 0.4, roughly equivalent to the fitted SALT2 light-curve parameter 𝑐 > 0.3). With the recently released Pantheon+ sample, there are 57 SNe Ia that were removed because of their high colour alone (with colours up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although previous works (Mandel et al 2011;Burns et al 2014) have found evidence for an anti-correlation between 𝑅 𝑉 and reddening or apparent colour, we generally do not find a strong effect of this nature (c.f. also Rose et al 2022). Whether splitting the sample into two (𝐵 −𝑉 ≤ 0.3 and 𝐵 −𝑉 > 0.3) or three (𝐵 −𝑉 ≤ 0.3, 0.3 < 𝐵 − 𝑉 ≤ 0.7, 𝐵 − 𝑉 > 0.7) bins of apparent colour, we find consistency in the mean 𝑅 𝑉 across the range of apparent colours.…”
Section: Discussionmentioning
confidence: 52%
“…Although previous works (Mandel et al 2011;Burns et al 2014) have found evidence for an anti-correlation between 𝑅 𝑉 and reddening or apparent colour, we generally do not find a strong effect of this nature (c.f. also Rose et al 2022). Whether splitting the sample into two (𝐵 −𝑉 ≤ 0.3 and 𝐵 −𝑉 > 0.3) or three (𝐵 −𝑉 ≤ 0.3, 0.3 < 𝐵 − 𝑉 ≤ 0.7, 𝐵 − 𝑉 > 0.7) bins of apparent colour, we find consistency in the mean 𝑅 𝑉 across the range of apparent colours.…”
Section: Discussionmentioning
confidence: 52%
“…Schlafly et al 2016), so logically 𝑅 𝑉 should vary between, and even within, different SNe host galaxies. This is considered in Chen et al (2022) for a sample of DES SNe Ia in redMaGiC galaxies, and Rose et al (2022) for a sample of Pantheon+ SNe Ia (Scolnic et al 2021;Brout et al 2022). Meldorf et al (2022) suggest that a correlation between host-𝑅 𝑉 and SNe Ia properties indicate that intrinsic scatter is driven by 𝑅 𝑉 .…”
Section: Introductionmentioning
confidence: 99%